2018
DOI: 10.31024/ajpp.2018.4.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Menthol causes reduction of Scopolamine induced Glutamatergic neurotoxicity and cognitive deficits

Abstract: Background: Enhancement in the lifespan of human beings in developed and developing countries has resulted in proportionate increase in the number of patients suffering from senile age-associated dementia. Memory impairment during aging is believed to be a consequence of decline in neuronal function and increase in neurodegeneration. Impaired neurotransmission at cholinergic synapses may contribute to the devastating loss of cognitive abilities in Alzheirmer's disease. It is suggested that a selective decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous research has also revealed the potential effects of 1,8-Cineole and α-Pinene in enhancing cognitive functions and memory process [ 60 , 61 ]. Menthol and menthone possess a greater activity to improving spatial memory and reducing cognitive defects that may be caused by scopolamine, which is obviously more represented in peppermint ( Mentha piperita ) [ 62 ]. The dominant composition of menthol/menthane in peppermint rather than in rosemary may explain the more potential anti-amnesic activity of peppermint oil extract compared with the rosemary of single-oil treatment [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has also revealed the potential effects of 1,8-Cineole and α-Pinene in enhancing cognitive functions and memory process [ 60 , 61 ]. Menthol and menthone possess a greater activity to improving spatial memory and reducing cognitive defects that may be caused by scopolamine, which is obviously more represented in peppermint ( Mentha piperita ) [ 62 ]. The dominant composition of menthol/menthane in peppermint rather than in rosemary may explain the more potential anti-amnesic activity of peppermint oil extract compared with the rosemary of single-oil treatment [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that menthol administration improves learning and memory in DE rats. The ameliorative potential of menthol might be attributable to an improvement in acetylcholine in the brain 28 .…”
Section: Discussionmentioning
confidence: 99%